2016
DOI: 10.1124/jpet.115.231456
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melatonin and 5-Methoxycarbonylamino-N-Acetyltryptamine on the Intraocular Pressure of Normal and Glaucomatous Mice

Abstract: Melatonin is a neurohormone that is produced not only by the pineal gland but also by several ocular structures. One of the main physiologic roles of melatonin is the reduction of intraocular pressure (IOP). Using both control C57BL/6J and glaucomatous DBA/2J mice as well as TonoLab tonometry, this study evaluated the effect of melatonin and 5-methoxycarbonylamino-N-acetyltryptamine (5-MCA-NAT) when glaucomatous pathology was fully established and compared pharmacological behavior in treated mice versus contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 31 publications
5
35
1
Order By: Relevance
“…In the DBA/2J, the reduction was equivalent to the one observed for other compounds in the same model. For instance, melatonin or its analogue 5-MCA-NAT reduced IOP between 29 and 32% in the DBA/2J and, as happened in the present paper, the effect on the normotensive animal was not so marked [27]. Other authors who used classical compounds such as the carbonic anhydrase inhibitor dorzolamide have demonstrated a similar effect [28], reducing IOP.…”
Section: Discussionsupporting
confidence: 81%
“…In the DBA/2J, the reduction was equivalent to the one observed for other compounds in the same model. For instance, melatonin or its analogue 5-MCA-NAT reduced IOP between 29 and 32% in the DBA/2J and, as happened in the present paper, the effect on the normotensive animal was not so marked [27]. Other authors who used classical compounds such as the carbonic anhydrase inhibitor dorzolamide have demonstrated a similar effect [28], reducing IOP.…”
Section: Discussionsupporting
confidence: 81%
“…This increase may explain the rise of melatonin in glaucomatous patients and opens the question of why, as melatonin concentrations are abnormally elevated in glaucomatous individuals, this substance cannot reduce IOP as should be expected. In this sense, many studies have reported the hypotensive action of melatonin and analogs either in normotensive and glaucomatous animal models [33,34] as well as in normotensive and ocular hypertensive human beings [12,35]. The reason why the exogenously added melatonin or analogs, produce a reduction in IOP, seems to be related to the dose reached in the aqueous humor.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a dysfunction of melatonin signaling triggers elevation of nocturnal IOP and loss of retinal ganglion cells (Figure ) . Additionally, exogenous melatonin and its analogues lower IOP in mammals, including humans (Figure ) . This ocular hypotensive effect seems to be mediated by ciliary body receptors (MT 2 and an unidentified receptor classically named MT 3 ) and final inhibition of ciliary chloride secretion .…”
Section: Melatonin and Aging‐related Eye Diseasesmentioning
confidence: 99%
“…212 Additionally, exogenous melatonin and its analogues lower IOP in mammals, including humans ( Figure 2). [213][214][215][216][217][218][219][220][221] This ocular hypotensive effect seems to be mediated by ciliary body receptors (MT 2 and an unidentified receptor classically named MT 3 ) and final inhibition of ciliary chloride secretion. 29,31,222,223 Furthermore, melatonergic compounds provide a sustained reduction in IOP through regulation of ciliary genes expression and potentiate the hypotensive action of classic antiglaucomatous drugs such as timolol and brimonidine.…”
Section: The Therapeutic Potential Of Melatonin In Glaucomamentioning
confidence: 99%